A Cross-sectional Study of Patients and Physicians on the Impact of Myeloproliferative Neoplasms on Patient Health: The Landmark Survey From Taiwan. (November 2021) - Chang, Cheng-Shyong; Chen, Chieh-Wen; Chiang, I-Ju; Ku, Fan-Chen; Lee, Yee-Ming; Siddiqui, Asif
Patients with myeloproliferative neoplasm (MPN), including myelofibrosis, polycythemia vera, and essential thrombocythemia, experience a pronounced symptom burden. This study aimed to collect information from physicians and patients in Taiwan to explore their perceptions regarding MPN, treatment goals, and satisfaction with disease management. A cross-sectional, online survey was conducted among patients and physicians from September 2018 to November 2018 in Taiwan as a subset of the expansion of the Landmark survey. Overall, 50 patients with MPN and 30 physicians participated in this study. The symptom burden was low, with the mean number of symptoms experienced being 1.8. The most frequent symptom per physicians' perception was fatigue, whereas it is not the most common symptom from MPN patients' perspective. Blood count was the key indicator to determine treatment success from patients' view, whereas presence of a new symptom was the key indicator from physicians' perspective. Concordant with previous studies, our study revealed a lack of alignment between physician and patient perceptions relating to treatment goals and disease management. Nevertheless, the physical, emotional, work/activities and financial impacts on patients were minimal in Taiwan.